1988
DOI: 10.1007/bf03010542
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of intubating doses of atracurium, d-tubocurarine, pancuronium and vecuronium in children

Abstract: A comparative evaluation of intubating doses of atracurium, d-tubocurarine, pancuronium and vecuronium in childrenTo determine the onset and recovery times and haemodynamie effects of intubating doses of atracurlum (04 mg.kg-r), dtubocurarine (0.8 mg.kg-t ), pancuronium (0.12 mg.kg-t ), and vecuronium (0.07 mg'kg-I )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…No other direct comparison between rocuronium and atracurium in children has yet been published, but our results are similar to those of a recent study comparing atracurium and rocuronium in adults [9]. Furthermore, in children of the same age group significant differences in clinical duration and recovery parameters had already been found for atracurium vs. vecuronium, which has a very similar molecular structure to rocuronium [10, 11]. In a review of other studies, which investigated separately either atracurium or rocuronium in young children, results can be found in clinical duration and recovery very similar to our own [4, 5, 7, 8].…”
Section: Introductionsupporting
confidence: 88%
“…No other direct comparison between rocuronium and atracurium in children has yet been published, but our results are similar to those of a recent study comparing atracurium and rocuronium in adults [9]. Furthermore, in children of the same age group significant differences in clinical duration and recovery parameters had already been found for atracurium vs. vecuronium, which has a very similar molecular structure to rocuronium [10, 11]. In a review of other studies, which investigated separately either atracurium or rocuronium in young children, results can be found in clinical duration and recovery very similar to our own [4, 5, 7, 8].…”
Section: Introductionsupporting
confidence: 88%
“…Sensitivity analyses did not show that the inclusion of studies with a high risk of bias 48,55,60,68,74,79,86,93,94,109 affected the conclusions.…”
Section: Credibility Of the Resultsmentioning
confidence: 89%
“…Electronic searches yielded 6345 potentially relevant trials, of which 71 (48 RCTs and 23 CCTs) eligible research papers (Figure 1 and Table S1) were identified, encompassing 4319 in the large majority ASA I‐II pediatric participants in 232 study arms 43–112 . We incorporated three RCTs that enrolled only a few ASA III patients 62,64,83 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in their study. A comparative evaluation of intubation doses of atracurium, d-tubocurarine, pancuronium, and vecuronium in children under halothane A few studies have been done in children examining anaesthesia was performed (15). The mean time to non-depolarizing muscle relaxants to expediate maximum twitch depression ranged from 2.1 min intubation.…”
Section: Discussionmentioning
confidence: 99%